Comparative Cephalometric Analysis of Angle Class II Division 1 Malocclusion Between Nepalese and Chinese Subjects - Sharma, Bishnu Prasad; Xin, Chang (Orthodontic Journal of Nepal, 2014)
Objective: To identify the craniofacial features of Nepalese and Chinese subjects with Angle Class II division 1 malocclusion; andto compare between Nepalese and Chinese samples and Nepalese gender groups. Materials & Method: The cephalometric radiographs were obtained from 96 Nepalese (mean ages16.34 ± 5.4 years) and 39Chinese (mean age 17.18 ± 7.1 years) subjects with Angle Cass II division 1 malocclusion. Ten skeletal, nine dental and three softtissue variables were investigated. Result: The craniofacial features between Nepalese and Chinese samples showed significant differences among fifteen of thetwenty-two variables studied; whereas in comparison between gender groups, six parameters were significantly different. Conclusion: Both samples showed well positioned maxilla, retrusive mandible and Class II skeletal tendency. In comparison,maxilla was more protrusive, mandible was more retrusive and overjet was more increased in Chinese. The Nepalese showedmore prominent nose and chin. DOI: http://dx.doi.org/10.3126/ojn.v4i1.11306 Orthodontic Journal of Nepal Vol.4(1) 2014; 17-